Coupled Reynolds–Mach–Thermal Dynamics in Vortex-Stabilized Meso-Scale Combustors: Implications for Efficiency and Stability - Azri Hariz Roslan,; Mohd Nawi, Mohd Al-Hafiz; Mohd Sharizan Md Sarip,; Chu Yee Khor ,; Muhammad Lutfi Abd Latif,; Mohammad Azrul Rizal Alias,; Mohd Fathurrahman Kamarudin,; Hazrin Jahidi Jaafar,; Mohd Danish, (International Journal of Integrated Engineering, 2026)
Meso-scale combustors have unique thermo-fluid challenges due to a high surface-to-volume ratio. Small changes in Reynolds number (Re) and Mach number (Ma) can have a big effect on how vortices behave, how heat moves, and how stable flames are. This study looks at how mass flow rate, Re, and Ma work together to change the temperature distribution in two vortex-stabilized combustor setups with different volumes. Current study works on high-fidelity CFD simulations using the RNG k–ε turbulence model with eddy dissipation chemistry over Re = 301.4–1153.8 (Ma